Athletic injuris of the wrist and hand. Part II: Overuse injuries of the wrist and traumatic injuries of the hand - Rettig, A. C. (The American Journal of Sports Medicine, 2004)
Hand and wrist injuries in sports are some of the most common injuries reported. This review discusses common overuse injuries of the wrist including tendon injuries such as de Quervain's syndrome, subluxation of the extensor carpi ulnaris, and the common dorsal carpal impingement syndrome. The main focus of this section is the discussion of traumatic injuries to the hand in the athlete. Included is a discussion and review of fractures of the phalanges and metacarpals, common proximal interphalangeal joint injuries, and thumb carpal metacarpal and metacarpophalangeal joint injuries. Emphasis is placed on more common injuries seen regarding diagnosis, indications for non-operative versus operative treatment, and time to return to athletic competition.